2020
DOI: 10.1103/physreva.101.022306
|View full text |Cite
|
Sign up to set email alerts
|

Locally distinguishing unextendible product bases by using entanglement efficiently

Abstract: Any set of states which cannot be perfectly distinguished by local operations and classical communication (LOCC) alone, can always be locally distinguished using quantum teleportation with enough entanglement resource. However, in quantum information theory, entanglement is a very valuable resource, so it leaves the following open question: how to accomplish this task more efficiently than teleportation, that is, design the local discrimination protocol using less entanglement resource. In this paper, we first… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…It costs 2 log 2 d ebits of entanglement resource in the above discrimination protocol. Protocols consuming less entanglement than the teleportationbased protocol attract much attention in recent years [37,43,47,51,53].…”
Section: (Iii)mentioning
confidence: 99%
“…It costs 2 log 2 d ebits of entanglement resource in the above discrimination protocol. Protocols consuming less entanglement than the teleportationbased protocol attract much attention in recent years [37,43,47,51,53].…”
Section: (Iii)mentioning
confidence: 99%
“…One can use entanglement as a resource to finish the locally distinguished protocol when the given set is locally indistinguishable. Such protocol is called the entanglement-assisted discrimination [29,[32][33][34][35][36][37][38][39][40]. It is also to quantify how many entanglement resource are needed to local distinguish the strongly nonlocal set constructed here in all bipartitions.…”
Section: Opss Of the Strongest Nonlocality In Five-partite Systemsmentioning
confidence: 99%
“…In this section, we provide a method of locally distinguishing UPBs constructed in Proposition 4 assisted by entanglement, because UPBs cannot be distinguished perfectly by LOCC alone [11]. When m = n ≥ 3 are odd, the UPB constructed from Proposition 4 can be perfectly distinguished by LOCC with a ⌈ m 2 ⌉ ⊗ ⌈ m 2 ⌉ maximally entangled state [17]. We will prove that any UPB from Proposition 4 can be perfectly distinguished by LOCC with a ⌈ m 2 ⌉ ⊗ ⌈ m 2 ⌉ maximally entangled state in Theorem 7.…”
Section: Application: Local Distinguishability Of Upbs By Entanglemen...mentioning
confidence: 99%
“…Then, local distinguishability with entanglement as a resource attracted more and more attention [12][13][14][15][16]. Recently, it has been shown that some UPBs constructed from tile structures in C m ⊗ C m can be distinguished by LOCC with a ⌈ m 2 ⌉⊗⌈ m 2 ⌉ maximally entangled state when m ≥ 3 is odd [17,18]. In particular, Ref.…”
Section: Introductionmentioning
confidence: 99%